Analisa Keefektifan Jaringan Local Area Network (intranet) Universitas Muria Kudus - Nurkamid, Mukhamad (Jurnal Sains dan Teknologi, 2011)
Local  networks,  or  often  known  by  the   term  intranet   is  how   to  connect   a  series   of   computer  organization (institution) is limited to a certain scope. Local Area network often known as the intranet is also referred to as the use of internet network for locally.In this study the authors tried to reveal a little more technology developed to build an intranet network at the University   of   Muria   Kudus   associated   with   the   management   and   utilization is managed   by   the   Technical Implementation Unit Planning Information System (UPT PSI) through the experimental test some components of  builders like Mikrotik, Cisco Router, Switch Manageable, Distribution Switch , Proxy Server and DNS Server.